2016
DOI: 10.1080/13636820.2016.1231214
|View full text |Cite
|
Sign up to set email alerts
|

E-assessment: challenges to the legitimacy of VET practitioners and auditors

Abstract: This research examines what practitioners in vocational education and training (VET) organisations and external auditors judge to be the key issues in the current and future delivery of e-assessment. Applying the framework of legitimacy theory, the study examined the tensions around the use and growth of eassessment in training organisations, and challenges to both training bodies and auditors around their legitimacy to operate. Forty-eight interviews, 10 focus groups and two industry workshops were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Dentro de la propia aplicación de los métodos activos de enseñanza, se encuentra el e-learning, usado principalmente en esta etapa educativa para el desarrollo de aquellos ciclos formativos que se imparten desde una modalidad a distancia. En este estudio los hallazgos permiten determinar que menos de la mitad del profesorado encuestado (42,26%) usa el e-learning en su labor docente, justificando el resto su nula utilización en sus carencias formativas en el ámbito digital, tal y como ya concluyeron Fuentes et al (2019) y su falta de confianza en el uso de este método de enseñanza, estando este motivo en contraposición a lo establecido en investigaciones anteriores donde se resalta una mejora del rendimiento (Brzezinska, 2018), de la comunicación (Callan et al 2016;García y Cabero, 2016) y del procesamiento la información (Kucheruk et al, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dentro de la propia aplicación de los métodos activos de enseñanza, se encuentra el e-learning, usado principalmente en esta etapa educativa para el desarrollo de aquellos ciclos formativos que se imparten desde una modalidad a distancia. En este estudio los hallazgos permiten determinar que menos de la mitad del profesorado encuestado (42,26%) usa el e-learning en su labor docente, justificando el resto su nula utilización en sus carencias formativas en el ámbito digital, tal y como ya concluyeron Fuentes et al (2019) y su falta de confianza en el uso de este método de enseñanza, estando este motivo en contraposición a lo establecido en investigaciones anteriores donde se resalta una mejora del rendimiento (Brzezinska, 2018), de la comunicación (Callan et al 2016;García y Cabero, 2016) y del procesamiento la información (Kucheruk et al, 2019).…”
Section: Resultsunclassified
“…Diversos estudios muestran que la combinación entre el enfoque e-learning y la Formación Profesional favorece el rendimiento (Brzezinska, 2018), la comunicación entre los diferentes colectivos (Callan, Johnston, Clayton y Poulsen, 2016;García y Cabero, 2016), el procesamiento y estructura de la información significativa (Kucheruk, Karaman, Karaman y Vinnikova, 2019) mediante el despliegue de acciones formativas no memorísticas-transmitivas (Cabreiro, Fernández y Arribi, 2017), basadas en la combinación de contenidos teóricos de alta calidad y actividades prácticas (Ugolini, Massetti, Sanesi y Pearlmutter, 2015;Widaningsih, Barliana, Aryanti y Malihah, 2018). No obstante, expertos como Dimache et al (2015) establecen que las habilidades de carácter tecnopedagógico tanto de los docentes como de los discentes establecen un punto de inflexión en este enfoque innovador, marcando su éxito o fracaso en la Formación Profesional.…”
Section: Introductionunclassified
“…Research in the tertiary sector has also shown that such an environment can have an impact on student success and retention, increase the achievement of learning outcomes and contribute towards a positive perception of the learning experience (Callan et al, 2016;Hellmundt & Baker, 2017). In their literature review of 12 studies into VET in the workplace, Mikkonen et al (2017) noted that friendly, reciprocal relationships also supported learning in workplace-based educational settings.…”
Section: Relationshipsmentioning
confidence: 99%
“…The resulting benefits for learners can be numerous, including being made to feel, ‘acceptable and legitimate’ (Bishop et al, 2009, p. 8) and being able to feel comfortable about making mistakes and learning from them (Hattie, 2012). Research in the tertiary sector has also shown that such an environment can have an impact on student success and retention, increase the achievement of learning outcomes and contribute towards a positive perception of the learning experience (Callan et al, 2016; Hellmundt & Baker, 2017). In their literature review of 12 studies into VET in the workplace, Mikkonen et al (2017) noted that friendly, reciprocal relationships also supported learning in workplace‐based educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic assessment or e-assessment is the use of information technology in assessment activities that provide flexibility and ease of access for its users so that the assessment is more interactive (Callan et al, 2016;Mimirinis, 2018;Rodríguez-Gómez et al, 2014;Stowell & Lamshed, 2011). Electronic assessment plays a very important role which can cover the entire assessment environment along with the development of information and communication technology (Adesemowo et al, 2016;Lafuente et al, 2014;Whitelock, 2010).…”
Section:  Introductionmentioning
confidence: 99%